2019
DOI: 10.1002/jpln.201800516
|View full text |Cite
|
Sign up to set email alerts
|

Detectability of degradable organic matter in agricultural soils by thermogravimetry

Abstract: Sustainable agricultural land use requires an assessment of degradable soil organic matter (SOM) because of its key function for soil fertility and plant nutrition. Such an assessment for practical land use should consider transformation processes of SOM and its sources of different origin. In this study, we combined a 120‐day incubation experiment with thermal decay dynamics of agricultural soils altered by added organic amendments. The aim was to determine the abilities and limits of thermal analysis as a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
(105 reference statements)
1
4
0
Order By: Relevance
“…Likewise, compost fertilisation also resulted in a slightly higher relative weight loss and ion intensity for CO 2 (m/z 44) in the same temperature intervals at both soil layers. The results of the present study are also in agreement with a recent study conducted by Tokarski et al (2019), who observed that farmyard manure results in thermal mass losses mainly around 450 °C. Previous studies using thermogravimetry (TG) and differential scanning calorimetry (DSC) analysis indicate that exothermic peaks up to 350 °C are related to decomposition of organic matter rich in labile aliphatic and carboxyl groups, whereas identified peaks up to approximately 500 °C represent dominance of stable aromatic component classes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Likewise, compost fertilisation also resulted in a slightly higher relative weight loss and ion intensity for CO 2 (m/z 44) in the same temperature intervals at both soil layers. The results of the present study are also in agreement with a recent study conducted by Tokarski et al (2019), who observed that farmyard manure results in thermal mass losses mainly around 450 °C. Previous studies using thermogravimetry (TG) and differential scanning calorimetry (DSC) analysis indicate that exothermic peaks up to 350 °C are related to decomposition of organic matter rich in labile aliphatic and carboxyl groups, whereas identified peaks up to approximately 500 °C represent dominance of stable aromatic component classes.…”
Section: Discussionsupporting
confidence: 93%
“…Whilst the mixture of grasses and legumes and the use of organic amendments often result in an increased SOC stock (Sainju et al, 2006;Jian et al, 2020), mixed results have been reported due to the use of grass or legume during the ley period phases as well as due to the application of different organic amendments source (Mazzoncini et al, 2011;Aguilera et al, 2013;O'Dea et al, 2013). This might be due to differences in biomass production, C:N ratios and lignin content of the crops in the rotation as well as persistence of the organic amendments source to degradability in soils (Tokarski et al, 2019;Zhou et al, 2019). In the organic rotation, along with the grass-clover ley periods, other legumes (e.g., peas and beans) and vegetables (e.g., cabbage, lettuces, onions, and carrots) were cultivated in an 8-year period (2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018), which might have provided the finest balance between biomass production and optimal C:N ratio inputs for SOC accumulation benefits.…”
Section: Discussionmentioning
confidence: 99%
“…During heating, the samples were ushed with an air ow of at least 200 ml/min at 76% relative humidity and 20°C. Further details can be found in [27,32,33,34].…”
Section: Methods Usedmentioning
confidence: 99%
“…This resulted in TML130 values higher than those expected in natural soils with the respective clay contents. Since the added fresh residues are biodegradable, the associated deviations decrease in proportion to the measured respiratory activity or degradation rate [33,34,41]. Fresh, unconverted, biodegradable organic substances, regardless of their chemical composition, can be quanti ed based on deviations between the measured TML and the TML calculated from the clay content.…”
Section: Thermal Decay Dynamics Of Soilsmentioning
confidence: 99%

Natural soils analysis for future land use

Siewert,
Krahl,
Schwitzky
et al. 2024
Preprint
Self Cite
“…With the rapid development of the composting industry, compost producers are focusing their attention on the effective utilization of energy in the production process and on improving the quality of compost by controlling the forced ventilation system [1]. Aerobic composting can rationalize the use of livestock manure and straw and alleviate environmental pollution [2][3][4][5]. The amount of aeration will affect the microbial activity in aerobic composting, thereby affecting the normal fermentation of aerobic compost and delaying the composting maturity process.…”
Section: Introductionmentioning
confidence: 99%